An Analysıs Of A Modernist Novel: Kırmızı Pelerinli Kent - Alkır, Yağmur (Bartın Üniversitesi, 2023)
Each era's view of life, humanity and the way it perceives reality is directly reflected in the artistic understanding of the time period in question. Until the late 19th century, the novel was the extension of Newtonian physics in literary aesthetics, leaning on reason and the concrete. The 19th century realist novel has a time-sequential flow that reflects the outside world exactly, but it does not contain any complexity. Thus, until the 20th century, the reader reads events in the novels that coincide with the reality of his/her own physical world and depend on cause-and-effect relationships. However, the new scientific developments that gained momentum in the 20th century began to call into question the main principles of Newtonian physics. This new understanding of reality finds its counterpart in 20th century aesthetics. This new understanding, which is called modernist literature, does not take the rational and logical as the only criterion by taking a critical attitude towards the general principles of modernism. The inner world of the individual, spiritual and moral values are emphasized. The author's free attitude gains importance against traditional patterns in aesthetic understanding. Thus, in the modernist novel, where the absolute power of reason is questioned, the classical novel understanding is abandoned and innovations are made in content and form. In our study, Aslı Erdoğan's novel Kırmızı Pelerinli Kent (1998) has been scrutinized by taking into consideration the possibilities provided to the author by the modernist novel understanding, first of all, after giving information about modernism and modernist novel understanding, modernist techniques were identified in the novel in question, and then the work was subjected to analysis under the titles of City and Slums, Alienation and Escape, Flaneur as Observing Subject.

Her çağın yaşama, insana bakışı ve gerçekliği algılama biçimi, söz konusu zaman kesitinin sanat anlayışına doğrudan yansır. 19. yüzyılın sonlarına kadar roman Newton fiziğinin edebiyat estetiğindeki uzantısı görünümünde olup akla ve somut olana yaslanmıştır. 19. yüzyılın realist romanı dış dünyayı birebir yansıtan, zamandizinsel bir akışa sahip olmakla birlikte bünyesinde hiçbir karmaşayı barındırmaz. Böylece okur 20. yüzyıla kadar romanlarda kendi fiziksel dünyasının gerçekliğiyle örtüşen, neden-sonuç ilişkisine bağlı olayları okur. Ancak 20. yüzyıla gelindiğinde ivme kazanan yeni bilimsel gelişmeler Newton fiziğinin ana ilkelerini de kuşkulu kılmaya başlamıştır. Bu yeni gerçeklik anlayışı 20. yüzyıl estetiğinde de karşılığını bulur. Modernist edebiyat olarak adlandırılan bu yeni anlayış modernizmin genel ilkelerine de eleştirel bir tavır ortaya koyarak akli ve mantıki olanı tek ölçüt olarak almaz. Bireyin iç dünyası, ruhsal ve manevi değerler ön plana çıkarılır. Estetik anlayıştaki geleneksel kalıplara karşı artık yazarın özgür tutumu önem kazanır. Böylece aklın mutlak gücünün sorgulanmaya başlandığı modernist romanda klasik roman anlayışı terk edilerek içerik ve biçimde yeniliklere gidilmiştir. Çalışmamızda Aslı Erdoğan'ın Kırmızı Pelerinli Kent (1998) adlı romanı, modernist roman anlayışının yazara sağladığı imkânlar göz önünde bulundurularak mercek altına alınmış, öncelikle modernizm ve modernist roman anlayışı hakkında bilgi verildikten sonra bahse konu romanda modernist teknikler tespit edilip ardından eser Kent ve Gecekondulaşma, Yabancılaşma ve Kaçış, Gözlemleyen Özne Olarak Flanör başlıkları altında incelemeye tabi tutulmuştur.
Modernist Bir Roman Çözümlemesi: Kırmızı Pelerinli Kent
Keywords: Modernist/Postmodernist Literature; Modern ve Postmodern Edebiyat